Pengaruh Informasi Managemen Dalam Pengelolaan Dana dan Pemberdayaan Masyarakat Gampong - Marah Sutan Rangkuti; Marzuki Marzuki; Agusmadi Agusmadi (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
The purpose of this study was to describe the management of Gampong Fund Management Information in empowering the gampong community and to find out some of the possible and hindering influences in managing gampong funds. This study used descriptive qualitative method. This activity was carried out in Ulee Pata Village, Jaya Baru Subdistrict, Banda Aceh Regency, by conducting interviews and observations to obtain the necessary data and collect information relating to the management of gampong fund management information that had been interpreted. The results of this study indicate that the gampong fund management process carried out by the gampong government has not been completely transparent, the gampong community has not actively participated, and village government officials are more dominant in planning activities and the implementation of gampong funds from 3 hamlets has not been active and still struggling on infrastructure development. The management of village funds has not been aligned towards community empowerment in the context of giving birth to economic income sources, but is still very large for infrastructure development. Empowerment activities are prioritized for physical empowerment such as road construction, rental housing, opening new roads and multi-purpose buildings, while empowering non-physical is associated with minimal training for residents in need. The results of the study indicate that the supporting factors of village fund management in empowering the village community in Ulee Pata Village are support for policy / regulation, socialization, facilities, and infrastructure. The inhibiting factor is a lack of human resources and a lack of community participation in the village.